(3QSGdI aj GdJQcIs - (3GdNhfLj , eMeO Hf fGeGhQ Hf YHO Gdedc, CaVd GdOjf CHh YHO Gddg,J (B646 (3g` s
(3ChdgG (B:s
(3CeG HYO aJM GdcdGe HMeO Gddg ajbhd CMbQ GdNOGe eMeO GdTgjQ HCaVd GdOjf JQcg Cfg ai SGda GdReGf cGf fbV ENaGA GdENhGf s
(3BNQgG (B:s
(3hJcGdja GdLejY ef hYdi GdKGfi jdRe NQhL Je GdLhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B22s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B122 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B73s
Keywords: (3GdeLGejYs